Short utterances in Japanese language conversation among Japanese and Malaysian tourist guides - Mamat, Roslina; Abd Rahim, Normaliza; Abdul Halim, Hazlina; Tajuddin, Farah (School of Media and Communication Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2012)
Aizuchi, feedback and insertion are the 3 important elements in a Japanese language conversation. Aizuchi and feedback can be categorized as short utterance. This paper discussed short utterance in a conversation between native speakers and non-native speakers of Japanese language based on writer’s research findings. This is because in general, students of Universiti Putra Malaysia (UPM) have problems in constructing a real-life conversation in Japanese language. This paper tried to analyze the conversational situation between two Malaysian tour guides and two Japanese tourists. The face-to-face conversation occured when the tour guides brought the tourists to Aquaria KLCC (G1&T1) and Istana Negara (G2&T2). This research intended to expose the conversation between the culture of native speaker and non-native speaker as a reference to students who are learning Japanese language.